Effect of the production cycle on the yield potential and nutritional quality of forage corn in the Comarca Lagunera - Granados-Niño, Jorge Alberto; Sánchez-Duarte, Juan Isidro; Ochoa-Martínez, Esmeralda; Rodríguez-Hernández, Karla; Reta-Sánchez, David Guadalupe; López-Calderón, Magali Jeaneth (Revista Mexicana de Ciencias Agrícolas, 2022)
The objective of this study was to evaluate the effect of the production cycle on the yield potential and nutritional quality of forage corn in the Comarca Lagunera. The experiment was established at the La Laguna Experimental Field of the National Institute of Forestry, Agricultural and Livestock Research, in Matamoros, Coahuila, Mexico. The hybrid corn SB-302 was used in the spring and summer agricultural cycles under a completely randomized block design with four repetitions during 2018, 2020 and 2021. The information was analyzed with the PROC MIXED of SAS using the agricultural cycle as a fixed effect and the year as a random effect. The following were evaluated: yields of green (GFY) and dry forage (DFY), dry matter (DM), crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), in vitro digestibility of NDF at 30 hours of incubation (DNDF-30 h), net energy of lactation (NEL), starch and lignin, potential milk production per tonne and per hectare, and yields of NDF, DNDF-30 h and NEL, starch and lignin. The GFY and DFY were higher in spring than in summer by 8.8 and 3.7 t ha-1, respectively. The production cycle did not affect DM, NDF, NEL, starch and lignin. However, for the spring cycle, the contents of CP, ADF and DNDF-30 h were higher than in the summer by 0.57, 1.98 and 7.87%, respectively. In addition, the potential milk production per tonne and yields of NDF, DNDF-30 h and NEL were higher in spring than in summer. In general, corn sown in spring had higher forage yields per hectare and with better fiber digestibility than corn sown in summer in the Comarca Lagunera.